M1 Monocyte Polarization and Deficient Immunomodulation in Preeclampsia - Romao-Veiga, Mariana [UNESP]; Devides, Amanda Carreira [UNESP]; Ribeiro-Vasques, Vanessa Rocha [UNESP]; Matias, Mariana Leticia [UNESP]; Gomes, Virginia Juliani [UNESP]; Romagnoli, Graziela Gorete; Peraçoli, Maria Terezinha Serrao [UNESP]; Peraçoli, Jose Carlos [UNESP] (Taylor & Francis, 2025)
INTRODUCTION: Preeclampsia (PE) is a specific pregnancy syndrome characterized by a systemic inflammatory response that may be dependent on the presence of danger molecules called damage-associated molecular patterns (DAMPs). High mobility group Box 1 (HMGB1) is a DAMP that shows possible interaction with haptoglobin and can be removed from circulation by the CD163 receptor. OBJECTIVE: This study aimed to evaluate the involvement of haptoglobin, HMGB1, and CD163 receptor in the systemic inflammatory response in pregnant women with PE. METHODS: Monocytes obtained from preeclamptic and normotensive (NT) pregnant women were evaluated for surface TLR4, RAGE, CD64, and CD163 receptors, as well as intracellular haptoglobin and HMGB1 expression by flow cytometry. RESULTS: Plasma levels of haptoglobin, HMGB1, and hemeoxygenase-1, as well as pro- and anti-inflammatory cytokines, were determined by the ELISA. Compared with NT group expression of TLR4, CD64, and RAGE receptors and intracellular HMGB1 and haptoglobin by monocytes was higher in women with PE, whereas extracellular CD163 expression was reduced in this group. Plasma concentrations of HMGB1, TNF-α, IL-1β, and IL-6 were higher in preeclamptic women, whereas the levels of haptoglobin, hemeoxygenase-1, and IL-10 were significantly lower. CONCLUSION: The elevated concentration of inflammatory cytokines and higher expression of TLR4, CD64, and RAGE receptors demonstrated that monocytes from PE women are polarized to the M1-like profile. Furthermore, the CD163 internalization and the absence of a high haptoglobin monocyte subset, along with decreased levels of haptoglobin, IL-10, and hemeoxygenase-1 in the PE group, indicates a deficiency in mechanisms that could regulate the intense inflammatory process associated with PE.